Parents and the NSU: Secrecy in National Socialist Youth Work in Denmark, 1932-1945. - Koegeler-Abdi, Martina (Scandinavian Journal of History, 2023)
This article examines the role of secrecy in relations between the NSU, the largest Danish national socialist youth organization, and parents. The NSU struggled to recruit and retain members from Danish families with and without national socialist convictions. By analysing how NSU media and internal correspondence framed parents' reluctance to join, this article traces the changing functions of NSU secrecy practices towards parents over time. Parents in Denmark could resist their children's membership during the German occupation as well, which prompted the NSU to use different secrecy practices to either circumvent or facilitate parental consent. In doing so, the organization had to engage with and across practices of family secrecy. This engagement offers new perspectives on everyday collaboration in occupied Denmark, as well as more general insights into the practical and conceptual tensions between national socialist youth work and parental authority.